LEADER’S PERSONAL ENTREPRENEURIAL CHARACTERISTICS OF FAMILY OWNED SMALL ENTERPRISES IN VAVUNIYA DISTRICT, SRI LANKA - Pushpanathan, A.; Lin, Z. (Rajiv Academy for Technology and Management, Mathura, India, 2008)
The leader of the firm has some personal entrepreneurial characteristics for achieving success in his/her business. The purpose of this article is to provide an explanation for the leader’s personal entrepreneurial characteristics in family owned small enterprises. Three factors –Achievement competencies, Planning competencies, and power competencies – were analyzed from 375 small entrepreneurs in Vavuniya District, Sri Lanka. And also mean value of individual variables were ranked in order of their importance.
Keywords: Leadership Styles; Family Owned Small Enterprise; Personal Entrepreneurial Characteristics